Reassessing the role of body composition in leg power performance in a young adult cohort / Ameer Hamzah ... [et al.]. - Hamzah, Ameer; Linoby, Adam; Sazali, Razif; Md Yusoff, Yusandra; Haziq, Amrun; Zulqarnain, Muhammad (Universiti Teknologi MARA, Negeri Sembilan, 2025)
Body Mass Index (BMI), waist circumference, and leg power are key indicators of physiological health, yet their interrelationships remain underexplored. Existing research largely focuses on athletes, leaving gaps in understanding recreational student populations. This study examines these correlations and identifies physiological characteristics in young adults, addressing limited research on the combined role of BMI, waist measurements, and leg power in this demographic.